2010
DOI: 10.1029/2009jf001495
|View full text |Cite
|
Sign up to set email alerts
|

From grain size to tectonics

Abstract: [1] Regional grain size trends in fluvial successions can reveal important information regarding the dynamics of sediment routing systems. Self-similar solutions for downsystem grain size fining have recently been proposed to explore how key variables, such as the spatial distribution of deposition, sediment discharge, and sediment supply characteristics, control spatial distribution of grain size in fluvial successions over time scales of 10 4 -10 6 years. We explore the sensitivity of these solutions to chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
207
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(221 citation statements)
references
References 65 publications
(169 reference statements)
13
207
0
1
Order By: Relevance
“…Time-averaged grain size distributions were collected from sites within the RRB and AHF (locations in Fig. 1A), using several in-situ and photographic Wolman point counts to give averages per 10 m 2 areas (see Duller et al, 2010;Whittaker et al, 2011). Present-day slope values of the base of variously aged Ogallala paleochannels, and the base of the RRB, were each constructed from an exponential fi t to scattered well and outcrop data (Swinehart et al, 1985;Diffendal, 1995, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Time-averaged grain size distributions were collected from sites within the RRB and AHF (locations in Fig. 1A), using several in-situ and photographic Wolman point counts to give averages per 10 m 2 areas (see Duller et al, 2010;Whittaker et al, 2011). Present-day slope values of the base of variously aged Ogallala paleochannels, and the base of the RRB, were each constructed from an exponential fi t to scattered well and outcrop data (Swinehart et al, 1985;Diffendal, 1995, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent outcrop studies demonstrate that the construction of sediment volume or mass budgets within the source-to-sink context of a sediment routing system can provide a powerful tool to quantitatively estimate the volume and grain size of sediment supply (e.g. Duller et al 2010;Whittaker et al 2011;Carvajal & Steel 2012;Michael et al 2013). The results are particularly useful if analysed in a mass-balance framework, in which the cumulative deposited volume of sediment in the downsystem direction is normalized by the total sediment volume (e.g.…”
Section: Sediment Supply Control On Parasequence-set Stackingmentioning
confidence: 99%
“…For instance, an increase in initial sediment discharge decreases the rate of initial grain size fining (Duller et al, 2010). Tectonic uplift in the source catchment will initially increase grain size at the proximal fan while increased precipitation will increase in the lateral extent of a coarse grained fan (Armitage et al, 2011).…”
Section: Source Catchment Influence On the Terrestrial Sinkmentioning
confidence: 99%
“…This is particularly relevant to extensional, strike-slip and foreland tectonic settings where the terrestrial sink is typically bounded by numerous but smaller high relief source catchment regions. The use of grain size in defining spatial trends, sediment supply characteristics and controls on fluvial successions over different spatial and temporal scales (Duller et al, 2010) is thereby complicated by the along strike variability observed in sediment discharge of the contributing source catchments. Grain size profiles in these systems may then represent a lateral coalescence of variability in source catchment discharge that contribute over different spatial and temporal scales.…”
Section: Source Catchment Influence On the Terrestrial Sinkmentioning
confidence: 99%